1996
DOI: 10.1007/bf02445148
|View full text |Cite
|
Sign up to set email alerts
|

Differences between August and Wistar rats in stress reactions and in the development of adaptation to stress

Abstract: Control and acutely stressed August rats have corticosterone levels 62% and 15% higher, respectively, than their Wistar counterparts, indicating that the activity of stress-mediating hypothalamic-pituitary-adrenal system in August rats is higher. On the other hand, the intensity of stress reactions and, consequently, the degree of activation of this system in August rats are 40-50% lower, as is the blood level of creatine phosphokinase. During adaptation to stress, August and Wistar rats show a similar decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…Thus, August rats were more resistant to stress than Wistar rats. These results are consistent with previously reported data showing that stress induced a less pronounced rise in blood creatine phosphokinase in August rats compared to Wistar rats [8].…”
Section: Resultssupporting
confidence: 96%
See 2 more Smart Citations
“…Thus, August rats were more resistant to stress than Wistar rats. These results are consistent with previously reported data showing that stress induced a less pronounced rise in blood creatine phosphokinase in August rats compared to Wistar rats [8].…”
Section: Resultssupporting
confidence: 96%
“…It should be emphasized that August and Wistar rats have various basal and poststress activities of the hypothalamo-pituitary-adrenocortical system and, therefore, different blood concentrations of glucocorticoids preventing stress-induced ulceration [1]. It was shown that basal and poststress contents of glucocorticoids in the blood of August rats are much higher than in Wistar rats [8,13].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Stress exposure induces a weaker stress response in August rats, which is accompanied by less severe damage (compared to Wistar rats) [6]. In August rats, activity of the stress-limiting system that decreases the stress response and attenuates stress-induced changes is higher than in Wistar rats [7,4].…”
mentioning
confidence: 99%